2021
DOI: 10.1111/hae.14155
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of cognitive‐behavioural therapy on emotional regulation and quality of life in children with Haemophilia

Abstract: and Background Data: Haemophilia has known as an inherited bleeding disorder accompanied by remarkable pain, emotional distress, and impaired quality of life (QoL) and emotional regulation. Psychological interventions, such as cognitivebehavioural therapy (CBT), have cost-effectiveness to promote emotional well-being, QoL and emotional regulation; however, they have been scarcely used in the treatment of haemophilia. Objectives of the Study: This research aimed at examining the effect of CBT on emotional regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Pain was reported more frequently by participants with significant anxious ( P = 0.004, Φ = 0.288) and depressive ( P = 0.001, Φ = 0.317) symptoms. Studies show that the more anxious hemophilia patients are, the more unpredictable their symptoms ( r = 0.001, P = 0.351) [7]. In another study of 81 participants who reported receiving on-demand coagulation factor therapy, 76 (94%) had at least one anxiety symptom.…”
Section: Anxietymentioning
confidence: 99%
See 4 more Smart Citations
“…Pain was reported more frequently by participants with significant anxious ( P = 0.004, Φ = 0.288) and depressive ( P = 0.001, Φ = 0.317) symptoms. Studies show that the more anxious hemophilia patients are, the more unpredictable their symptoms ( r = 0.001, P = 0.351) [7]. In another study of 81 participants who reported receiving on-demand coagulation factor therapy, 76 (94%) had at least one anxiety symptom.…”
Section: Anxietymentioning
confidence: 99%
“…Because high stress can be a factor in internal bleeding in patients with hemorrhagic disorders, this factor can deprive a person of life activities [3,5]. Studies have shown that patients with the highest levels of stress, anxiety, and depression experience pain with the highest intensity and that patients with severe pain have more stress, anxiety, and depression [7]. For this reason, appropriate use of coping strategies can help patients manage the stress associated with the disease [4].…”
Section: Stressmentioning
confidence: 99%
See 3 more Smart Citations